COMPERTIVE ESTIMATION OF INFLUENCE OF ADEMOL AND NIMODIPINE - Khodakovskiy, O.A.; Zhaboiedova, N.V.; Рокунець, І.Л. (World of Medicine and Biology, 2016)
In experiments on the rats with model of intracerebral hemorrhage of middle level of heaviness (introduction of own blood in subarachnoid space of 0.1 ml/100 g) was seen twice reduction of blood circulation in region of internal carotid artery in first 96 hours after modeling of pathology. Experimental Therapy industrial design ampoule 1.0% solution of 1-adamantyletyloksy-3-morpholino-2-propanol hydrochloride ("Ademol-Darnitsa" Darnitsa, Ukraine), relatively effective dose of 2 mg / kg intravenously every 24 hours for 4 days model of hemorrhagic stroke, similar to nimodipine (30 mkg/kg) prevented the decrease in cerebral hemodynamics. Thus, at the end of the experiment on the background of the introduction of "Ademol" indicator cortical volumetric flow rate remained higher relative to control group of animals Pathology average of 30.5%. Stimulatory effect "Ademol" on blood flow in the cerebral cortex, is an important part of its neuroprotective action in hemorrhagic stroke. Given that the study drug than stimulating effect on cerebral hemodynamics, as a modulator of NMDA-receptor activity - is promising further in-depth preclinical evaluation of its effectiveness in the treatment of stroke.